PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING SEBAGAI UPAYA PENINGKATAN HASIL BELAJAR SISWA PADA KOMPETENSI MENERAPKAN PRINSIP-PRINSIP BEKERJASAMA DENGAN KOLEGA DAN PELANGGAN - Vitria Puri Rahayu, ; Sri Purwaningsih, (Pendidikan Ekonomi, 2012)
This study applies the class action research (PTK). This study is done to get the data about the learning process using role playing learning model to increase students Activities during the learning process, since this role playing model tends to student centered. While, the teachers ability to handle the role playing learning method is increased in each cycle. On the first cycle is 2,4 means good enough and in second cycle is 3,2 which means average. The application of the role playing learning model also can increase students activities during the learning process. It is shown by the average point in each cycle. In the I cycle is 2,4 which means good enough and increased 3,1 in the  second cycle which means average. The application of the role playing learning model also can increase the learning outcome that can be observed trough the post test result in the first cycle is 74,9 and in the second cycle is 81,5. In other words, the employment of the role play learning model can increase students learning outcome, the average points from the 1st post test is incresed in the 2nd post test and the average points is above the classical KKM, that is 75.